Re-Paving the Road Built by Chemistry: A Challenge to Biochemistry and Biotechnology - Iglesias, Alberto Alvaro (2015)
This Editorial deals with the current critical situation reached by high standard technology based on petroleum for energy and materials. It is resumed the advance of chemistry, mainly petrochemistry and organic synthesis, to develope fuels, lubricants, polymers and many high value materials. It is analyzed that success reached with these developments has a opposite side determined by problems arose from limited oil reserves, recalcitrant characteristics of synthetic molecules to degradation and the unbalance provoked on gases in the atmosphere causing green-house effect and climate change. A view is described where answers to the crisis have to come from conversion of petrochemistry to processes based on the use of bio-tools, as it is stated by the biorefinery approach. In this scenario, the call for basic research in biochemistry and molecular biology has never been greater.